2007
DOI: 10.1213/01.ane.0000253029.67331.8d
|View full text |Cite
|
Sign up to set email alerts
|

The Common Chemical Motifs Within Anesthetic Binding Sites

Abstract: Anesthetic binding to proteins involves amphipathic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 31 publications
4
64
0
Order By: Relevance
“…Several protein structures that have been solved in the presence of anesthetics suggest that they may prefer amphipathic environments (61). Additionally, aromatic residues have been shown to interact with halothane in photo-labeling studies (13).…”
Section: Discussionmentioning
confidence: 99%
“…Several protein structures that have been solved in the presence of anesthetics suggest that they may prefer amphipathic environments (61). Additionally, aromatic residues have been shown to interact with halothane in photo-labeling studies (13).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor mutation studies suggest that high-affinity propofol binding of GABA A receptors occurs at sites that are distinctly different from those that bind low-affinity volatile anesthetics, such as isoflurane [2] . Low-affinity binding sites are postulated to be amphipathic and water filled pockets within the receptor [3,4] . At least in the case of N-methyl-D-aspartate (NMDA) receptors, this low-affinity protein binding is subject to a cut-off effect associated with molar water solubility, but not molecular structure or size [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analysis has shown that IGAs modulate synaptic transmission in the central nervous system, rather than axonal conduction, and the effects of IGAs are remarkably synapse-specific and may vary among agents. IGA effects on the brain circuitry involved in sleep (hypothalamicbrain stem-thalamic loops) and memory (hippocampusamygdala-cortical loops) are currently the subject of intense study (Franks, 2008).We now know that IGAs are in fact relatively selective, that they act by binding to proteins, and that they do so by occupying small cavities (Bertaccini et al, 2007). In many cases, the relevant proteins are ion channels, and the effect of IGA binding to these allosteric sites is to alter the gating of these channels by physiological stimuli, presumably by altering the thermodynamic equilibrium between open and closed states of the channel.…”
mentioning
confidence: 99%
“…We now know that IGAs are in fact relatively selective, that they act by binding to proteins, and that they do so by occupying small cavities (Bertaccini et al, 2007). In many cases, the relevant proteins are ion channels, and the effect of IGA binding to these allosteric sites is to alter the gating of these channels by physiological stimuli, presumably by altering the thermodynamic equilibrium between open and closed states of the channel.…”
mentioning
confidence: 99%
See 1 more Smart Citation